Embodied healing a dance movement center as sanctuary for mental well-being - Laride, Jessa-Bel P.; Sicam, Olivia Alma G. (Quezon City College of Architecture, University of the Philippines Diliman, 2024)
Anxiety, Depression, PTSD, and Alcohol use disorders are some of the most common mental illnesses that happen after someone experiences a traumatic and negative event, and they remain a major mental health issue around the world, affecting all individuals, including those who live in the Philippines, which has a lot of different cultures. This research explores the potential of dance therapy studios as sanctuaries for survivors of mental health issues to cope with their unique challenges. Recognizing the relationship between architecture and mental health. However, the absence of specialized spaces for dance therapy creates challenges and raises important questions about architectural solutions to create safe, therapeutic, and empowering places for people recovering from mental health issues. The chosen site in Ususan, Taguig City, Philippines, strategically positions itself as a potential hub for medical tourism as it is close to residential, institutional, commercial, and open spaces that users could easily access. Key findings show that full design considerations are needed, including spatial analysis, color psychology, and adding natural elements to make the therapeutic potential better: Because the subject is so sensitive, data comes from online journals, research, and insights from dance therapists. Using secure, empowering, and therapeutic design principles and the “Groove” concept, the research envisions dance movement centers as transformative spaces, offering solace and a unique pathway for mental health issue recovery, especially for those experiencing anxiety, depression, alcohol use disorder, and PTSD. It can end mental health stigma, lay the foundation for future interdisciplinary studies, advance education, and present a holistic perspective on mental health and well-being, envisioning dance movement centers as sanctuaries where embodied healing becomes a central focus in the recovery process.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Include appendices
Keywords: Dance therapy -- Taguig City; Dance schools -- Taguig City; Mental health